MEDICINAL PLANTS USEFUL FOR MALARIA THERAPY IN OKEIGBO - Odugbemi, Tolu O.; Akinsulire, Odunayo R.; Aibinu, Ibukun E.; Fabeku, Peter O. (African Journal of Traditional, Complementary and Alternative Medicines, 2006)
There is increasing resistance of malaria parasites to chloroquine, the cheapest and commonly used drug for malaria in Nigeria. Artemisin, a product from medicinal plant indigenous to China, based on active principle of Artemisia annua, has been introduced into the Nigerian market. However not much has been done to project antimalaria properties of indigenous medicinal plants. This study thus, has the main objective of presenting medicinal plants used for malaria therapy in Okeigbo, Ondo State, South west Nigeria. Focus group discussions and interview were held about plants often found useful for malaria therapy in the community. Fifty species (local names) including for example: Morinda lucida (Oruwo), Enantia chlorantha (Awopa), Alstonia boonei (Ahun), Azadirachta indica (Dongoyaro) and Khaya grandifoliola (Oganwo) plants were found to be in use for malaria therapy at Okeigbo, Southwest, Nigeria . The parts of plants used could either be the barks, roots, leaves or whole plants. The recipes also, could be a combination of various species of plants or plant parts. This study highlights potential sources for the development of new antimalarial drugs from indigenous medicinal plants found in Okeigbo, Nigeria.